Feeding behaviour, predatory functional responses and trophic interactions of the invasive Chinese mitten crab (Eriocheir sinensis) and signal crayfish (Pacifastacus leniusculus). (5th February 2016) - Rosewarne, Paula J; Mortimer, Robert J.G.; Newton, Robert J.; Grocock, Christopher; Wing, Christopher D.; Dunn, Alison M.
Summary: Freshwaters are subject to particularly high rates of species introductions; hence, invaders increasingly co‐occur and may interact to enhance impacts on ecosystem structure and function. As trophic interactions are a key mechanism by which invaders influence communities, we used a combination of approaches to investigate the feeding preferences and community impacts of two globally invasive large benthic decapods that co‐occur in freshwaters: the signal crayfish ( Pacifastacus leniusculus ) and Chinese mitten crab ( Eriocheir sinensis ). In laboratory preference tests, both consumed similar food items, including chironomids, isopods and the eggs of two coarse fish species. In a comparison of predatory functional responses with a native crayfish ( Austropotamobius pallipes ), juvenile E. sinensis had a greater predatory intensity than the native A. pallipes on the keystone shredder Gammarus pulex, and also displayed a greater preference than P. leniusculus for this prey item. In outdoor mesocosms ( n = 16) used to investigate community impacts, the abundance of amphipods, isopods, chironomids and gastropods declined in the presence of decapods, and a decapod >gastropod >periphyton trophic cascade was detected when both species were present. Eriocheir sinensis affected a wider range of animal taxa than P. leniusculus . Stable‐isotope and gut‐content analysis of wild‐caught adult specimens of both invaders revealed a wide and overlapping range of diet items including macrophytes, algae, terrestrial detritus, macroinvertebrates and fish. Both decapods were similarly enriched in 15 N and occupied the same trophic level as Ephemeroptera, Odonata and Notonecta. Eriocheir sinensis δ 13 C values were closely aligned with macrophytes indicating a reliance on energy from this basal resource, supported by evidence of direct consumption from gut contents. Pacifastacus leniusculus δ 13 C values were intermediate between those of terrestrial leaf litter and macrophytes, suggesting reliance on both allochthonous and autochthonous energy pathways. Our results suggest that E. sinensis is likely to exert a greater per capita impact on the macroinvertebrate communities in invaded systems than P. leniusculus, with potential indirect effects on productivity and energy flow through the community.